Effectiveness between Static Stretching and Kneading Massage on Lowering Heart Rate among University Silat athletes - Sani, Muhammad Haziq Mat; Shapie, Muhamad Nizam Mohamad; Ihsan, Nurul; Okilanda, Ardo; Putra, Juanda; Samsudin, Hazim; Nawai, Nasru Syazwan (International Martial Arts and Culture Journal, 2023)
Background and aim. The purpose of this study is to determine the effectiveness of static stretching versus kneading massage in lowering heart rate (HR) recovery among silat athletes.Methods.  Forty male subjects aged 18–25 years old were divided into two groups: the static stretching group (CG) and the kneading massage group (EG). The subjects completed pre- and post-test sessions involving a 3-minute step-up box test followed by a recovery treatment program. Heart rate monitor (HRM) measurements were taken immediately after treatment.Results.  The analysis revealed significant differences between both groups in reducing heart rate. The percentage of heart rate recovery for the kneading massage group (EG) was 33%, compared to 21% in the static stretching group (CG). The kneading massage group (48.30 ± 8.51 bpm) achieved a greater reduction in heart rate compared to the static stretching group (27.80 ± 6.90 bpm).Conclusions. Kneading massage is more effective than static stretching in enhancing short-term heart rate recovery among silat athletes.